1983
DOI: 10.1029/rs018i006p00851
|View full text |Cite
|
Sign up to set email alerts
|

Observations of stimulated electromagnetic emissions in ionospheric heating experiments

Abstract: Induced sideband modes, due to stimulated electromagnetic emissions in the ionosphere, have been observed around the frequency of a high‐intensity HF radio wave transmitted from the Heating ionospheric modification facility near Tromsø, Norway. The new observational technique used amounts to analyzing the received HF spectrum directly without utilizing any diagnostic radar. It appears that we have in this way been able to identify the parameteric decay instability and, possibly, the stimulated Brillouin backsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(39 citation statements)
references
References 11 publications
2
37
0
Order By: Relevance
“…It was shown that the intensity of the DM component is greater under O-mode pumping. This result is consistent with previous results by Thidé et al, 1983. In addition, under X-mode pumping, the intensity and number of observed SEE features is less then under O-mode pumping.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…It was shown that the intensity of the DM component is greater under O-mode pumping. This result is consistent with previous results by Thidé et al, 1983. In addition, under X-mode pumping, the intensity and number of observed SEE features is less then under O-mode pumping.…”
Section: Discussionsupporting
confidence: 83%
“…The utilization of the different pump wave polarizations leads only to a change in the efficiency of the generation of the SEE that was found during the early phase of SEE investigations (Thidé et al, 1983). The predominant O polarization of DM was preserved in both cases of the pump wave polarizations used.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…If the pump frequency f H is not extremely close to an electron gyroharmonic, there are strong SEE signals downshifted from f H with a strongly pronounced maximum downshifted by the lower hybrid frequency f LH . Such downshifted maximum, f DM f H A f LH , in the SEE spectra is well known (Thide , 1983). It is common knowledge (Leyser et al, 1989) that the lower hybrid frequency is approximately 8 kHz in the ionosphere above Tromsù.…”
Section: Phenomena During the Second Activationmentioning
confidence: 94%
“…The behavior of the BUM relative to the presence or absence of striations is more ambiguous. The BUM appears continuously over a range of pump frequencies starting at -10 kHz below the gyroharmonic frequency [Frolov et al, 1996] and continuing to a maximum frequency (fpmx) --100 kHz above the gyroharmonic frequency [Thid• et al, 1983;Stubbe et al, 1984Stubbe et al, , 1994Leyser et al, 1989Leyser et al, , 1990Leyser et al, , 1993Frolov et al, 1996]. Over this range of pump frequencies, striations are present everywhere except for a narrow range of frequencies surrounding the gyroharmonic frequency.…”
Section: Tionsmentioning
confidence: 99%